Surface‐Enhanced Raman Nanoprobes with Embedded Standards for Quantitative Cholesterol Detection. Issue 11 (23rd August 2018) - Jiang, Xin; Tan, Ziyang; Lin, Li; He, Jing; He, Chang; Thackray, Benjamin D.; Zhang, Yuqing; Ye, Jian
Abstract: Cholesterol is an essential molecule for many processes in the human body and many diseases such as hypertension, coronary heart disease, atherosclerosis, and lipid metabolism dysfunction can be detected in their early stages by monitoring intracellular cholesterol levels. Herein, metallic surface‐enhanced Raman scattering (SERS) core–shell nanoparticles with an embedded standard are designed for nondestructive detection of H2 O2 and cholesterol. A classical least squares (CLS) spectral fitting method allows one to accurately extract the SERS signals of internal standards and target molecules from the multiplexed spectra. The embedded internal standard can be used to calibrate the SERS signals, removing fluctuations induced by differing measurement conditions and local states of the nanoparticles, such as aggregation. Thus, SERS signal reproducibility is improved and a better linear relationship in the working curve of detection is achieved. Using these SERS nanoprobes quantitative detection of H2 O2 and cholesterol in solution and inside live cells at a single‐cell level is demonstrated. Abstract : Metallic core–shell nanoparticles with an embedded standard are designed as surface‐enhanced Raman scattering (SERS) nanoprobes for nondestructive quantitative detection of H2 O2 and cholesterol in solution and inside fixed and live cells at a single‐cell level.